THE FUNCTIONAL CHARACTER OF Auricularia auricula CRUDE POLYSACCHARIDES: ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY - Rizki Rabeca Elfirta; Iwan Saskiawan (Research Center for Biology-Indonesian Institute of Sciences, 2020)
The food stuffs can be clasified as functional food since the foods can improve the human health. One of them are the food stuffs which have function as antioxidant and antibacterial. These activities were studied on crude polysaccharides from Auricularia auricula. The sample was subsequently isolated using hot water and 1 M NaOH to obtain water and alkali soluble of crude polysaccharides. The antioxidant activity was evaluated using β-caroten-linoleat assay. The results showed that the alkali soluble of crude polysaccharides had the highest antioxidant activity (85.82%) at 350 μg/ml. The water and alkali soluble of crude polysaccharides from A.auricula were evaluated for their antibacterial activity using disc diffusion method. The alkali soluble of crude polysaccharides was found to have the highest antibacterial activity at 100 mg/ml against Staphylococcus aureus InaCC B4 and Escherichia coli InaCC B5 with clear zone values of 3.18 mm and 5.10 mm, respectively. The findings indicated that the alkali soluble of crude polysaccharides from A. auricula could potentially be used in part of well-balanced diets and could be considered as a potential source of natural antioxidant and antibacterial products.